Praktik Pemanfaatan Kecerdasan Buatan dalam Pembelajaran: Studi Pengalaman Guru di Sekolah - Ahmad Khoirul Anam Firdaus; Siti Nurul Hidayah; Muhammad Arif Billah Santoso (Genta Bangsa : Jurnal Ilmu Pendidikan, 2026)
Artificial intelligence (AI) integration in education has become a significant global trend, yet empirical evidence regarding teachers' direct experiences remains limited in the Indonesian context. This study aims to explore and describe teachers' experiences in utilizing AI-based technology in learning processes at school. The research employed a qualitative phenomenological method with in-depth interviews and document analysis involving twelve teachers from various educational levels in Lampung Province. Findings reveal four main dimensions: teachers' AI literacy, forms of AI utilization in learning design, challenges in implementation, and the impact on learning quality. The results indicate that AI adoption improves efficiency in lesson planning and material personalization, although challenges related to digital access and competency remain significant barriers. This study concludes that structured and sustainable professional development is needed to optimize AI use in Indonesian educational settings.